2023
DOI: 10.1002/smll.202203357
|View full text |Cite
|
Sign up to set email alerts
|

Wide‐Field Three‐Dimensional Depth‐Invariant Cellular‐Resolution Imaging of the Human Retina

Abstract: Three‐dimensional (3D) cellular‐resolution imaging of the living human retina over a large field of view will bring a great impact in clinical ophthalmology, potentially finding new biomarkers for early diagnosis and improving the pathophysiological understanding of ocular diseases. While hardware‐based and computational adaptive optics (AO) optical coherence tomography (OCT) have been developed to achieve cellular‐resolution retinal imaging, these approaches support limited 3D imaging fields, and their high c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Similarly, Lee and his colleagues reported that the exposed lattice in Zr-based UiO-67 (Cubic, a = 26.92 Å) closely resembled the hexagonal lattice observed in the ab-plane of Ga-based MIL-88D (Figure 2f). [113] Therefore, the exposed hexagonal lattice of UiO-67 as a template, facilitating the perpendicular growth of MIL-88D in the c-direction. SEM images showed that UiO-67 had the shape of a 3D octahedron, and the growth of MIL-88D on the template of UiO-67 yielded an urchin-like UiO-67@MIL-88D with a uniform elemental distribution of zirconium and gallium in Figure 2g-i.…”
Section: Valence Statementioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Lee and his colleagues reported that the exposed lattice in Zr-based UiO-67 (Cubic, a = 26.92 Å) closely resembled the hexagonal lattice observed in the ab-plane of Ga-based MIL-88D (Figure 2f). [113] Therefore, the exposed hexagonal lattice of UiO-67 as a template, facilitating the perpendicular growth of MIL-88D in the c-direction. SEM images showed that UiO-67 had the shape of a 3D octahedron, and the growth of MIL-88D on the template of UiO-67 yielded an urchin-like UiO-67@MIL-88D with a uniform elemental distribution of zirconium and gallium in Figure 2g-i.…”
Section: Valence Statementioning
confidence: 99%
“…Meanwhile, it will expose the labile coordination bonds to coordinating molecules and decrease the mechanical stability of the MOFs. Fe-MOF@Ga-MOF Fe-MIL-88B Ga-MIL-88B Cationic radius [108] Fe-MOF@In-MOF Fe-MIL-88B In-MIL-88B Cationic radius [109] Cu(II)-tpt-on-Cu(I)-tpt Cu(I)-tpt Cu(II)-tpt Valence state of the metal ions [111] MIL-88B-on-UiO-66 UiO-66 MIL-88B Valence state of the metal ions [112] UiO-67@MIL-88D UiO-67 MIL-88D Valence state of the metal ions [113] MIL-68@MIL-68-NO HKUST-1@MOF-5 HKUST-1 MOF-5 Lattice match [129] HKUST-1@Ga-MIL-88B HKUST-1 Ga-MIL-88B Lattice match [130] Fe-BDC-on-MOF-801…”
Section: Linker Sizementioning
confidence: 99%
See 1 more Smart Citation